Dielectric relaxation, diffuseness and conductivity behavior of transition metal-ion substituted SrBi2Nb2O9 synthesized by chemical route - Adak M.K.; Dhak P.; Singh A.; Sen S.; Dhak D. (My University, 2025)
Nanocrystalline Sr0.5A0.5Bi2Nb2O9 powders (A = Co2+, Ni2+, Cu2+; abbreviated as SCoBN, SNiBN, SCuBN respectively) were synthesized by chemical route. Powder X-ray diffraction study confirmed the tetragonal phase when calcined at 650 °C for 2 h. Average crystallite and particle size were calculated to be between 15 and 25 nm. The tetragonality was increased from Co2+ to Ni2+ to Cu2+-substituted SrBi2Nb2O9. SCuBN showed highest dielectric constant of 1344 and a loss in the order of 10−2 when measured at 100 kHz. SNiBN and SCuBN showed relaxation behavior and maximum diffusivity of 1.88 was observed for the later composition. The activation energy was calculated from DC and AC conductivity. Hysteresis loops displayed by the ceramics giving rise to a remnant polarization (Pr) of 0.046 μC/cm2 and a coercive field (Ec) of 495 V/cm for SCuBN. Both SCuBN and SNiBN showed high fatigue endurance values with a fatigue free behavior up to 105 switching cycles. © 2015, Springer Science+Business Media New York.